(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Waste management has become a big issue in a society where waste can easily be ignored and neglected. This situation becomes worst when the world population has grown rapidly and improper waste management system is not catered to. This paper is an attempt to provide an Automatic Recycle Dustbin System (ARDS) with GSM Module for the waste management system. The ARDS allows sorting the recyclable waste such as metal, paper and general waste. The Arduino microcontroller is employed to initialize the sensors to detect different types of waste. The experimental results have shown that the proposed ARDS able to accurately 95% sorting the recyclable waste such as aluminum cans and beverage tetra packs. In addition, the GSM Module successfully notifies the level of ARDS to the users such as ‘full’ and ‘25% full’. The results show that the ARDS is reliable to be implemented in a modern waste management system that allows the Recycle, Reuse and Reduce (3Rs) activities.